Gathering Diverse Perspectives to Tackle "Wicked Problems": Racial/Ethnic Disproportionality in Educational Placement. Issue 1 (4th July 2019) - NeMoyer, Amanda; Nakash, Ora; Fukuda, Marie; Rosenthal, Jill; Mention, Najeia; Chambers, Valeria A.; Delman, Deborah; Perez, Gilberto; Green, Jennifer G.; Trickett, Edison; Alegría, Margarita
Abstract: Among students receiving behavioral health and special education services, racial/ethnic minority students are consistently overrepresented in settings separate from general classrooms. Once separated, many young people struggle to improve academically and face significant difficulty upon trying to return to a general education setting. Given the complex, ongoing, and multifaceted nature of this challenge, racial/ethnic disproportionality can be identified as a "wicked problem, " for which solutions are not easily identified. Here, we describe our community‐engaged research efforts, eliciting perspectives from relevant partners in an ongoing dialogue, to better integrate diverse stakeholders' perspectives when attempting to address such disparities. We conducted focus groups and qualitative interviews with members of three stakeholder groups: community‐serving organizations, individuals with lived experience of behavioral health conditions, and state‐level policymakers, with a shared interest in addressing racial and ethnic disparities. Participant responses illustrated the "wickedness" of this problem and highlighted the need for additional supports for students, families, and school personnel, increased collaboration across relevant systems and agencies, and reduced barriers related to funding. Overall, this methodology bridged differing perspectives to develop, in concert with our partners, a shared language of the problem and a core set of issues to consider when seeking to effect change. Highlights: Racial/ethnic disparities in educational placement represent a complex, "wicked" problem. Eliciting perspectives from diverse stakeholders can generate ideas for addressing wicked problems. Stakeholder recommendations targeted students, school personnel, systems/agencies, and communities.